2007
DOI: 10.1111/j.1464-410x.2007.07318.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of microvessel density with microvascular invasion, metastasis and prognosis in renal cell carcinoma

Abstract: OBJECTIVE To clarify the significance of microvessel density (MVD) in a retrospective investigation the relationship between the pattern of MVD (reflecting angiogenesis), and tumour stage, grade, size, and occurrence of microvessel invasion (MVI), metastasis, and cancer‐specific survival (CSS) in patients who had surgery for renal cell carcinoma (RCC). PATIENTS AND METHODS Vessels were labelled in sections of formalin‐fixed, paraffin‐embedded tissues from 54 RCCs by CD34 immunohistochemistry. The mean MVD, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 18 publications
3
41
3
4
Order By: Relevance
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 99%
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 99%
“…For most of solid tumours, microvessel density (MVD) correlates with poor prognosis. However, MVD remains a controversial prognostic predictor for RCC (Kirkali et al, 2001;Sabo et al, 2001a;Suzuki et al, 2001;Dekel et al, 2002;Kinouchi et al, 2003;Yildiz et al, 2008;Qian et al, 2009), a significant contributory factor being that blood vessels in RCC may be regarded as being monolithic in structure and function, which might not accurately reflect the functional diversity based on microvessel differentiation and location. Mature blood vessels are usually covered by pericytes, and pericyte coverage is regarded as an indicator of vascular maturation (Gerhardt and Semb, 2008).…”
Section: Hai-lun Zhan Xin Gao* Xiang-fu Zhou Xiao-yong Pu De-juanmentioning
confidence: 99%
“…Los grandes sinusoides anastomó-ticos se contabilizaron como un vaso único. Los resultados se expresaron como número máximo de vasos por mm 2 de tejido tumoral [21][22][23] .…”
Section: Métodos Inmunohistoquímicosunclassified